Potencial de contribuição da cadeia de açúcar para a matriz energética do estado do Paraná - Leite, Luzia Aparecida Bispo (2019)
Brazil obtains its electric energy by road sources, with hydraulics being the largest. Other energy sources complement the country's energy matrix, such as biomass, from energy crops and are considered clean and safe.Among the biomasses, the sugarcane plant stands out in the country and in the state of Paraná, being considered totally usable, from alcohol to its residues, vinasse, bagasse, straw and filter cake. Its cultivation was adapted in the regions north, northwest and northeast of the state. In order to contribute to the sugar and alcohol industry, through the free software Quantum Gis, maps were generated, from the area of cultivation, production, productivity, generation of bagasse and vinasse in the state of Paraná. For regression analyzes, vinasse and bagasse generation data were used for the municipalities of each mesoregion, with municipalities with zero generation being eliminated. And in Excel, with official data from the area for sugarcane cultivation and its production, the productivity of sugarcane was estimated to be the generation of alcohol, generation of bagasse, vinasse, straw and filter cake, applying formula mathematics, of proportional quantities to estimate the quantity of each variable. Concluding, after data studies, the decrease in the production of sugarcane, alcohol and its residues. In addition, the possible generation of 215.04MWh for bagasse, 26.1MWh for vinasse and 204.8MWh for straw.